(untitled) - Leggett, Glenn H. (Englewood Cliffs, N.J., 1978)
Content included: Basic grammar, basic sentence faults, manuscript mechanics, punctuation, larger elements, effective sentences, writing summaries and examinations,..
Keywords: English language,Tiếng Anh,English language; Rhetoric,Ngữ pháp,Grammar